Collisional Broadening within a Hadronic Transport Approach - Branislav Balinovic; Renan Hirayama; Hannah Elfner (Universe, 2023)
We explore the emergence of the collisional broadening of hadrons under the influence of different media using the hadronic transport approach SMASH (Simulating Many Accelerated Strongly interacting Hadrons), which employs vacuum properties and contains no a priori information about in-medium effects. In this context, we define collisional broadening as a decrease in the lifetime of hadrons, and it arises from an interplay between the cross-sections for inelastic processes and the available phase space. We quantify this effect for various hadron species, in both a thermal gas in equilibrium and in nuclear collisions. Furthermore, we distinguish the individual contribution of each process and verify the medium response to different vacuum assumptions; we see that the decay width that depends on the resonance mass leads to a larger broadening than a mass-independent scenario.